The health risk practices of women sex workers (Research, Society and Development, 2020)
Objective: to discuss, based on a reflection, about the risk practices of women sex workers, and their health conditions. Methodology: descriptive, qualitative and reflective study, based on the critical reading of scientific materials about the impact of risky practices on the health of women sex workers. Results: risky practices for women sex workers directly affect their physical, psychological, emotional health, and strategies are needed to ensure their full exercise of work without any circumstances that make it impossible. Conclusion: it is necessary that educational activities, such as lectures, workshops, conversation circles be intensified in order to guarantee satisfactory health, and inhibiting the health risk practices of women sex workers.